Partial Nephrectomy of Renal Cell Carcinoma in Horseshoe Kidney with Assistance of Intraoperative Retrograde Pyelogram: A Case Report and Literature Review (Journal of Kidney Cancer, 2026)
Horseshoe kidney (HSK), characterized by the fusion of two kidneys forming a U-shape, presents intricate challenges in renal anatomy and poses a unique landscape for the development of renal cell carcinoma (RCC). This abstract delves into the case of a 74-year-old male with HSK who also developed RCC, where the employment of intraoperative retrograde pyelogram (RP) played a pivotal role in enhancing surgical preci-sion. The patient’s complex tumor was successfully resected through meticulous identification and dissection. A comprehensive literature review reveals the significance of laparoscopic and robotic surgeries in treating RCC within HSKs, with 3D-reconstruction aiding in surgical planning. While advancements in imaging technologies have improved surgical outcomes, the underexplored utility of intraoperative RP stands out. RP provided real-time insights into the renal pelvis anatomy, guiding the surgical team in navigating intricate structures and ensuring optimal recon-struction post-tumor excision. The discussion underscores the challenges posed by RCC in HSKs, importance of preoperative 3D-reconstruction and angiography in surgical planning, and the critical role of intraoperative RP in mapping renal pelvis anatomy. Unlike conventional imaging methods, RP offers dynamic visualization of the renal drainage system, safeguarding against inadvertent closures and enhancing surgical precision. The successful utilization of RP in this case not only facilitated safe tumor resection but also highlighted its potential in managing unclear renal structures. In conclusion, the integration of intraoperative RP in surgical interventions for RCC within HSKs proves instrumental in enhancing surgical precision and navigating complex anatomical variations. By emphasizing the importance of real-time imaging guidance, surgeons can optimize treatment outcomes for individuals with RCC in the challenging context of HSK anomalies.